Live cell tracking of symmetry break in actin cytoskeleton triggered by abrupt changes in micromechanical environments - Inoue, Shigeto; Frank, Victoria; Kaufmann, Stefan; Tanaka, Motomu (Biomaterials science, 2015)
With the aid of stimulus-responsive hydrogel substrates composed of ABA triblock copolymer micelles, we monitored the morphological dynamics of myoblast (C2C12) cells in response to an abrupt change in the substrate elasticity by live cell imaging. The remodeling of actin cytoskeletons could be monitored by means of transient transfection with LifeAct-GFP. Dynamic changes in the orientational order of actin filaments were characterized by an order parameter, which enables one to generalize the mechanically induced actin cytoskeletons as a break of symmetry. The critical role that acto-myosin complexes play in the morphological transition was verified by the treatment of cells with myosin II inhibitor (blebbistatin) and the fluorescence localization of focal adhesion contacts. Such dynamically tunable hydrogels can be utilized as in vitro cellular micro-environments that can exert time-dependent stimuli to mechanically regulate target cells.
Gesehen am 09.06.2020